As culturas dos Jovens do povo Magüta: descolonização dos Imaginários sociais, TI Magüta Umariaçu/AM - Araújo, Itamar Neco (Brasil, 2024)
This work presents a description, explanation, identification and analysis of the cultures of young Magüta and the decolonization of social imaginaries. I sought to describe the importance of the socio-geohistorical context of the Indigenous Land Magüta Umariaçu/Am. The research was carried out based on narratives and interviews with young people from the village. I analyzed the importance of Young Magüta for valuing their culture, the teachings and rules that are imposed by YO'I and IPI as processes for valuing their identity through socialization, which are marked as positive attitudes within the people, as is the initiation ritual, I also present Etchire Magüta and Rejicars as institutions that are responsible for processes of socialization and transmission of ancestral knowledge. I analyzed and realized that through socialization, young Magüta activate their imagination to deconstruct any type of stereotypes, prejudices and stigmas that are imposed by white people that harm cultural and political development, using the term “decolonial”, and in their ways of social participation and construction of its policies. Therefore, in view of their cultures, traditional young people experience in groups among young people with the same ideologies, such as the existence of superiority, considering traditional knowledge is superior to colonialist knowledge, therefore, it strengthens ancestral spirituality and from these perspectives young people dedicate themselves to prepare to fight for their rights, their inclusion and to strengthen their cultures and politics in the village.